Isolation of microcrystalline cellulose from corn stover with emphasis on its constituents: Corn cover and corn cob. (2020) - Singh, H.K.; Patil, T.; Vineeth, S.K.; Das, S.; Pramanik, A.; Mhaske, S.T.
Abstract: This study investigates the isolation of microcrystalline cellulose (MCC) from corn stover biomass by acid hydrolysis method with aiming towards its constituents viz; corn cover and corn cob. The process comprises chemical treatments with varying concentrations to optimize the concentrations of chemical reactants. The cellulose crystals produced with optimized concentrations of 2% w/v NaOH, 2% w/v acidified NaClO2 and 10% v/v H2 SO4 gives the yield of 25.90%, 29.60% and 39.32% of cellulose from corn cover, corn cob and corn stover respectively. The isolated needle-shaped MCC from corn stover showed the particle dimension in the range of 1.3–2.5 µm solely with a narrow distribution.